Kajian Morfodinamika Muara Sungai Batang Masang Kecamatan Kinali Dengan Memanfaatkan Sistem Penginderaan Jauh - Sendra Saputra; Novelisa Suryani; Heny Mariati (Universitas Tamansiswa Padang, 2022)
The purpose of this research was to analyze the land use change and identify the morphodynamics of the coastline at estuary in Batang Masang River from 2015 to 2021. These changes determined through remote sensing by utilyzing sentinel-2 satellite imagery in 2015 and 2021. Land use change known by using supervised classification with the maximum likelihood classification method. Meanwhile, to determine the morphodynamics of the coastline, doing by digitization on screen land use map based on the lowest tide from the bathymetry map. This study obtained results in form the largest change land use the addition of open land area of 27.64 ha, then followed by a reduction in forest land area of 12.26 ha, while the smallest change land use was the reduction of scrub was 7.73 ha (1.79 %). Furthermore, there was a reduction in the length of the coastline, namely 0.43 km, abrasion of 9.68 ha and accretion of 11.52 ha occurred. Thus the most dominant morphodynamics process in the Batang Masang River estuary is influenced by sea waves and river discharge.